PPARs modulate cardiac metabolism and mitochondrial function in diabetes - Lee, Ting-Wei (J Biomed Sci, 2017)
Diabetic cardiomyopathy is a major complication of diabetes mellitus (DM). Currently, effective treatments for diabetic cardiomyopathy are limited. The pathophysiology of diabetic cardiomyopathy is complex, whereas mitochondrial dysfunction plays a vital role in the genesis of diabetic cardiomyopathy. Metabolic regulation targeting mitochondrial dysfunction is expected to be a reasonable strategy for treating diabetic cardiomyopathy. Peroxisome proliferator-activated receptors (PPARs) are master executors in regulating glucose and lipid homeostasis and also modulate mitochondrial function. However, synthetic PPAR agonists used for treating hyperlipidemia and DM have shown controversial effects on cardiovascular regulation. This article reviews our updated understanding of the beneficial and detrimental effects of PPARs on mitochondria in diabetic hearts.